PERANCANGAN DAN PELATIHAN PENGELOLAAN WEBSITE PONDOK PESANTREN ASSUBKIYAH KABUPATEN BANDUNG - Mohammad Isa Pramana Koesoemadinata; Didit Widiatmoko Soewardikoen; I Dewa Alit Dwija Putra; I Gusti Agung Rangga Lawe; Irfan Dwi Rahadianto (Politeknik Negeri Sriwijaya, 2021)
Assubkiyah Islamic boarding school in Nagrak Village, Bandung Regency, is an Islamic educational institution that accepts many new students. As a traditional Islamic educational institution, this school has contributed a lot in creating a new generation with noble morality. In accordance with the times and for information and promotion purposes, this school has had a website before, so its remote location is not a problem. However, due to lack of management skills, website knowledge and funding, the website is neglected and not updated. This can lead to misinformation for people who need information about the program and activities of school, it can also have an impact on decreasing the number of prospective students. Based on that situation, a team from the Faculty of Creative Industries, Telkom University, took the initiative to design an information website regarding the Assubkiyah Islamic Boarding School, along with its management training for the staff and students. Hopefully, that after this program takes place, the website can be optimized into a medium that makes it easier for the public and prospective students to get information about education organized by the Assubkiyah Islamic Boarding School.